IMPLEMENTASI DATA MINING DALAM MEMPREDIKSI TRANSAKSI PENJUALAN MENGGUNAKAN ALGORITMA APRIORI (STUDI KASUS : PT.ARMA ANUGERAH ABADI CABANG SEI RAMPAH) - Harahap, Paujiah Nur; Sulindawaty, Sulindawaty (STMIK KAPUTAMA, 2020)
Data mining is a operation that involves collecting and using data to find patterns or relationships from large data sets. Data mining has been implemented in various fields, one of which is in the sale of bakery products. The company can find out the buyer's interest by using data mining to process data on sales of bakery products. This study discusses information retrieval from bread sales transaction data using data mining with a priori algorithms. Apriori algorithm is a type of association rule (Association rules) in determining the combination pattern of item set and association rules at PT. Arma Anugerah Abadi Sei Rampah Branch, namely with the highest value of support and confidence are the Chocolate Cheese Wrap Bread and the Pres coconut Wrap Bread with a support value of 17% and a confidence value of 77%.